Trends and research mapping of mathematical mindset publications: A bibliometric analysis using Vosviewer - Yusuf Adhitya; Nurmala Setianing Putri; Bill Chairy Rizki Bustaren; Jay Fie Paler Luzano (Journal Focus Action of Research Mathematic (Factor M), 2025)
In addition to the theory and implementation, the description of research trends and the direction of development of mathematical mindset research still needs to be explored. The study aims to find trends and mapping from the mathematical mindset research development. The method used is bibliometric with the help of MS Excel and VosViewer. The metadata is 995 articles indexed by Google Scholar from 2019 to 2025, obtained from Publish or Perish by entering the keyword "mathematical mindset." The results show a sharp decline in post-2020 publications, the most in 2020, as many as 272, but plummeting to 3 in early 2025. This decline occurred due to policy changes after the pandemic, reallocating funding to digital learning, and competition for research priorities. Boaler's book related to Mathematical Mindset 2022 became the publication with the most citations (2329). The VOSviewer analysis results identified four main clusters, with the mathematical mindset being in cluster three. In addition, it found the potential for a weak connection with technological terms, which could be a new research direction. The results of this study provide optimism and opportunities for mathematical mindset research to be more associated with other terms that can be connected, especially in mathematics education research.